2021
DOI: 10.35808/ijeba/671
|View full text |Cite
|
Sign up to set email alerts
|

Street Entrepreneurship in the Wake of Covid-19: The Dilemma of Street Vending and Strategies for Endurance

Abstract: Purpose: To determine how street vendors can endure and sustain their livelihoods under the restrictive conditions of Covid-19 management in Zimbabwe. Although entrepreneurship takes a widespread conception, one of its forms is characterized by informality like street vending. Despite local authorities' attempts to designate vending areas to decongest urban centers, street vendors always attempt to find their way back to the central business districts (CBD) in Zimbabwe. Designated areas are necessary, but vend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Additionally, the role of information asymmetry and digital literacy issues in hindering scheme access resonates with the broader literature on financial inclusion and technology adoption among marginalized populations (Khan & Bhandari, 2022;Aggarwal, 2022;Siwela & Njaya, 2018 [24-29]. However, the study also identified nuanced insights that complement existing knowledge, such as the diversity in utilization patterns among vendors and the need for tailored capacity-building initiatives to enhance scheme uptake [30][31][32][33].…”
Section: Comparison With Literature Review Findingsmentioning
confidence: 64%
“…Additionally, the role of information asymmetry and digital literacy issues in hindering scheme access resonates with the broader literature on financial inclusion and technology adoption among marginalized populations (Khan & Bhandari, 2022;Aggarwal, 2022;Siwela & Njaya, 2018 [24-29]. However, the study also identified nuanced insights that complement existing knowledge, such as the diversity in utilization patterns among vendors and the need for tailored capacity-building initiatives to enhance scheme uptake [30][31][32][33].…”
Section: Comparison With Literature Review Findingsmentioning
confidence: 64%
“…Based on the research findings, policy suggestions for the protection of street vendors are summarized in the fifth part. Chigudu (2021) has found that given their miserable, unreliable, and anxious incomes, street hawkers 4 cannot simply access appropriate COVID-19 private protective equipment (PPE) like sanitisers and masks, let alone apply meaningful social distancing. For street vendors working under ruthless conditions with unreliable or no water supplies, enhancing personal hygiene, like hand washing with water and soap to prevent COVID-19 infection, is rather challenging.…”
mentioning
confidence: 99%